Effect of the Piston Crown Contour on the Fluid Flow of Diesel Engine using Biodiesel B30 Based on Simulation - Semin; Cahyono, Beny; Baskoro, Taruno Ganggas Daruadji (International Journal of Marine Engineering Innovation and Research, 2025)
Diesel engines are categorized into internal combustion engines. On the internal combustion engine, combustion occurs in the combustion chamber. The combustion process requires three main elements: fuel, air, and heat from compression. The combustion process on the internal combustion engine will affect engine performance or emissions. The engine used is Yanmar TF85MH, one cylinder, four-stroke, direct-injection with B30 fuel palm oil. This study analyzes the effect of the piston bowl depth on the resulting fluid flow. To get the data, the author using the ANSYS software. The current piston bowl depth is 15,5 mm. In this study, model variation with addition and reduction of +2, +1, 0, -1, and -2 (in mm). The results of the simulation show that the highest swirl ratio occurs in case 5 with a value of -1,15, the highest temperature occurs in case 4 with a value of 2373°K, and the highest heat release rate occurs in case 4 with a value of 3,25x108 erg/degree.